Cashew crop propagation - Geraldo Martins, Antonio Baldo [UNESP]; Correia da Silva, Adriana de Castro; Chiamolera, Fernando Marcelo (Soc Brasileira Fruticultura, 2019)
The cashew tree, a genuinely Brazilian fruit tree, is grown mainly because of its nuts and cashew nut shell liquid (CNSL), widely used in industry. Of great food importance, the cashew apple also presents economic representativeness in Brazil. With great variability, the culture has recently begun researches for improvement, with selection of new clones, more productive and with specific purpose. Usually propagated from seeds to produce new orchards, which has been replaced by vegetative propagation using the seed only for rootstocks production. Vegetative propagation by lateral grafting is the mainly technique used to multiplicated this crop, but various clonal propagation techniques, such air layering and tissue culture have been attempted. The last one, however, needs further studies because of their high costs.
Keywords: cashew nut; cashew apple; native fruit